L’Observatoire photographique du paysage du PNR des Vosges du Nord : de l’œuvre à l’action - Raphaële Bertho; Frédéric Pousin (Projets de Paysage)
For more than 25 years, the Photographic Observatories of the Landscape have been set up within regional structures in charge of environmental management and changes in the landscape and built-up areas. In this article, we study the case of the Photographic Observatory of the Vosges du Nord Regional Nature Park which was created in 1997 and is still active today. The permanent presence of the structure and of the stakeholders makes it possible to analyse over a period of more than 20 years the changes in an observatory through its successive uses. At the crossroads between cultural and regional development policies, the Observatory experienced a series of changes in the modalities of its management and in its objectives. The analysis of these transformations makes it possible to identify three paradigms which coexisted over the years due to the flexibility offered by the photographic medium, which is a document as well as a work of art, and the different meanings attributed to the notion of the landscape. The following registers emerged: that of the representation (visual or symbolic), that of the inventory (with the intent of systematically indexing the landscapes of the regional nature park), and that of the mediation between stakeholders and inhabitants.